2021
DOI: 10.1055/s-0041-1723993
|View full text |Cite
|
Sign up to set email alerts
|

Hypospadias and the Use of the Ages and Stages Questionnaire to Evaluate Neurodevelopmental Status of Boys with Hypospadias

Abstract: Introduction Placental insufficiency is one of the reasons for the reduction of hormone production. Thus, if one of the suspected causes of hypospadias is placental insufficiency, then the neurodevelopmental status of boys with hypospadias may be impaired. The aim of this study was to evaluate the neurodevelopmental status of boys with hypospadias and guide the parents of those who need support to related departments for early intervention. Materials and Methods Boys were divided into two groups, tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…However, a cohort study developed by Ortqvist et al (18) indicated that psychiatric symptoms (i.e., affective, suicidal, and anxiety symptoms) were more common in hypospadias patients than the healthy controls, but these psychiatric illnesses did not have e markedly difference between the two groups as well as between the severity or phenotype groups. Besides, no statistical significant difference was observed in the four included studies (10,14,15,21). In line with these findings, Mureau et al (30) demonstrated that psychiatric impairments did not differ obviously between patients with hypospadias surgery and those who underwent surgery for an inguinal hernia.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, a cohort study developed by Ortqvist et al (18) indicated that psychiatric symptoms (i.e., affective, suicidal, and anxiety symptoms) were more common in hypospadias patients than the healthy controls, but these psychiatric illnesses did not have e markedly difference between the two groups as well as between the severity or phenotype groups. Besides, no statistical significant difference was observed in the four included studies (10,14,15,21). In line with these findings, Mureau et al (30) demonstrated that psychiatric impairments did not differ obviously between patients with hypospadias surgery and those who underwent surgery for an inguinal hernia.…”
Section: Discussionmentioning
confidence: 89%
“…According to the above evidence, six included studies ( 10 , 15 , 18 , 20 , 21 , 34 ) explicitly showed that there was a non-significant association between hypospadias and psychiatric illnesses, regardless of whether underwent the surgery or not, while eight included studies ( 11 – 14 , 16 , 19 , 23 , 24 ) suggested that patients with hypospadias had a significantly higher risk of psychiatric comorbidity than the controls. Since almost all the patients had received hypospadias surgery, when choosing the operative age, the psychiatric comorbidity should be considered comprehensively to achieve the optimal therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations